2020
DOI: 10.1515/hf-2019-0248
|View full text |Cite
|
Sign up to set email alerts
|

A study on the GA-BP neural network model for surface roughness of basswood-veneered medium-density fiberboard

Abstract: Roughness is an important property of wood surface and has a significant influence on the interface bonding strength and surface coating quality. However, there are no theoretical models for basswood-veneered medium-density fiberboard (MDF) by fine sanding from existing research work. In this paper, the basswood-veneered MDF was fine sanded with an air drum. Orthogonal experiment was implemented to study the effects of abrasive granularity, feed rate, belt speed, air drum deformation and air drum pressure on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…To better represent the degree of disorder among the urbanization subsystem and the ecology subsystem in Table 1, the coupling degree model of (2) is introduced [18]as follows:…”
Section: Coupling Degree Modelmentioning
confidence: 99%
“…To better represent the degree of disorder among the urbanization subsystem and the ecology subsystem in Table 1, the coupling degree model of (2) is introduced [18]as follows:…”
Section: Coupling Degree Modelmentioning
confidence: 99%
“…They showed that the response surface model can be used for single-and multi-objective optimization. Meanwhile, a simulation model for the surface roughness was established by Wu et al 12 back-propagation (BP) neural network based on the genetic algorithm (GA-BP neural network), for medium-density fiberboard ground by metal-matrix composites. That work indicated that a GA-BP neural network can be used to predict the changes in surface roughness under different grinding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…BP neural network model [17,18], genetic algorithm model [19,20], support vector machine model [21], decision tree method [22]and time series method [23] were commonly used prediction methods at present. However, BP neural network had some defects such as local optimization, irrelevant to physical meaning, strong dependence on training data and slow convergence speed, which hindered its application in practical engineering [17,19]. Strong macro search and global optimization capabilities were the characteristics of genetic algorithm (GA) [20].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed GPU-based training of BP neural network was tested on a breast cancer data, which shown a significant enhancement in training speed [16]. BP neural network model [17,18], genetic algorithm model [19,20], support vector machine model [21], decision tree method [22]and time series method [23] were commonly used prediction methods at present. However, BP neural network had some defects such as local optimization, irrelevant to physical meaning, strong dependence on training data and slow convergence speed, which hindered its application in practical engineering [17,19].…”
Section: Introductionmentioning
confidence: 99%